2020
DOI: 10.1007/s12250-020-00308-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Existence of SARS-CoV-2 in COVID-19 Patients: Host Immunity, Viral Virulence, and Transmissibility

Abstract: COVID-19 patients can recover with a median SARS-CoV-2 clearance of 20 days post initial symptoms (PIS). However, we observed some COVID-19 patients with existing SARS-CoV-2 for more than 50 days PIS. This study aimed to investigate the cause of viral clearance delay and the infectivity in these patients. Demographic data and clinical characteristics of 22 long-term COVID-19 patients were collected. The median age of the studied cohort was 59.83 ± 12.94 years. All patients were clinically cured after long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
0
24
0
5
Order By: Relevance
“…There have been instances of COVID-19 patients who remained positive for SARS-CoV-2 by reverse transcription real-time polymerase chain reaction (RT-PCR) test for up to three months [95][96][97]98]. Other studies have documented cases of prolonged SARS-CoV-2 shedding in the respiratory tract via quantitative RT-PCR for up to four months [99,100].…”
Section: Pathological Inflammationmentioning
confidence: 99%
“…There have been instances of COVID-19 patients who remained positive for SARS-CoV-2 by reverse transcription real-time polymerase chain reaction (RT-PCR) test for up to three months [95][96][97]98]. Other studies have documented cases of prolonged SARS-CoV-2 shedding in the respiratory tract via quantitative RT-PCR for up to four months [99,100].…”
Section: Pathological Inflammationmentioning
confidence: 99%
“…This is the exact mechanism described as immunotolerance during virus-host adaptation. In a study that investigated the immune response of patients with long-term SARS-CoV-2 infections extending to 50 days from onset, clinically cured with an absence of related symptoms, it was shown that decreased IFNγ production by NK cells and low neutralizing antibodies might favor SARS-CoV-2 long-term existence together with low viral load and weak viral pathogenicity [70] . Accordingly, NK cells may contribute to SARS-CoV-2 clearance, and the decrease in IFNγ-expressing NK cells might delay viral clearance in these patients favoring viral persistence for a long time in a latent form.…”
Section: Patterns Of Ifnγ Action In Sars-cov-2 Virus Infectionmentioning
confidence: 99%
“…CoV-2 by reverse transcription real-time polymerase chain reaction (RT-PCR) test for up to three months (Carmo et al 2020;Kandetu et al 2020;X. Wang et al 2020b).…”
Section: Unresolved Inflammationmentioning
confidence: 99%